Social Media Optimization for Healthy Lifestyle Promotion Campaigns - Ardelia, Talitha Mega; Cahaya, Yohanes Ferry (Dinasti International Journal of Management Science, 2025)
Abstracts are written in one paragraph using standard Indonesian with enhanced spelling. Social media plays a significant role in promoting a healthy lifestyle to the wider community. With its wide reach and ability to deliver information in various formats, platforms such as Instagram, TikTok, Facebook, and YouTube are effective tools to raise awareness and encourage changes in people's health behavior. This study aims to analyze the potential, challenges, and strategies for optimizing social media in a healthy lifestyle campaign. The research method uses a qualitative approach with a literature study. The results of the study show that social media is not only effective as a means of delivering health information, but also functions to build a mutually supportive online community. Strategies such as selecting the right platform, collaborating with influencers, and presenting interesting and interactive content have been shown to increase audience engagement. Factors such as content quality, consistency, and relevance of information influence the success of a promotional campaign. Campaigns through social media have positive impacts, such as increasing public awareness of the importance of a healthy diet, regular exercise, and mental health balance. In addition, people are also more active in health programs organized by various parties. This study concludes that social media can be optimized as an effective tool to promote a healthy lifestyle, as long as it is supported by the right strategy and evidence-based content.